Upaya Peningkatan Pengetahuan Kesehatan Bayi Dan Balita Tentang Pentingnya Imunisasi - sitti hasriani, sitti hasriani (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2024)
Children are the nation's next generation who must be prepared in terms of knowledge, skills and health. The immunization program is the provision of immunization which is an effort to provide immunity to babies and children by inserting vaccines into the body so that the body makes anti-substances to prevent certain diseases. Health improvement is essentially an effort carried out by all components of the Indonesian nation which aims to increase awareness, willingness and ability to live healthily for everyone in order to achieve a level of public health. The aim of this community service activity is to increase mothers' knowledge about the importance of immunization in Kelurahan Nenang, Kecamatan Penajam, Kabupaten Penajam Paser. Community service was carried out by 32 mothers. The method used in this activity is providing material using media in the form of PowerPoint and leaflets. The results obtained were that the mother was able to understand the information presented well and was very enthusiastic about participating in this health education activity. In conclusion, the health education carried out can increase mothers' knowledge about the importance of immunization for babies and toddlers